Epistasis Activation Contributes Substantially to Heterosis in Temperate by Tropical Maize Hybrids - Sang, Zhiqin; Wang, Hui; Yang, Yuxin; Zhang, Zhanqin; Liu, Xiaogang; Li, Zhiwei; Xu, Yunbi (Frontiers in Plant Science, 2022)
Epistasis tremendously affects the performance of superior maize hybrids. In this study, a multiple-hybrid population was designed consisting of three hybrid maize sets that showed different degrees of inter-parental divergence, generated by crossing 28 temperate and 23 tropical inbred lines with diverse genetic backgrounds. Among the 1,154 tested hybrids, heterosis increased steadily as the heterotic genetic distance increased, whereas miparent heterosis was significantly higher in the temperate by tropical hybrids than in temperate by temperate hybrids. Genome-wide prediction and association mapping (GWAS) were performed for grain weight per plant (GWPP) and days to silking (DTS) using 20K high-quality SNPs. A total of 33 and 420 epistatic QTL were identified for GWPP and DTS, respectively, in temperate by tropical hybrids. Protein-protein interaction network and gene-set enrichment analyses showed that epistatic genes were involved in protein interactions, which play an important role in photosynthesis, biological transcription pathways and protein synthesis. We show that the interaction of many minor-effect genes in the hybrids can activate the transcription activators of epistatic genes, resulting in a cascade of amplified yield heterosis. The multiple-hybrid population design enhanced our understanding of heterosis in maize, providing insight into an acceleration of hybrid maize breeding by activation of epistatic effects.